1977
DOI: 10.1037/h0077330
|View full text |Cite
|
Sign up to set email alerts
|

Role of the hippocampus in blocking and conditioned inhibition of the rabbit's nictitating membrane response.

Abstract: Bilateral aspiration of the dorsal hippocampus produced a disruption of blocking of the rabbit's nictitating membrane response in Kamin's two-stage paradigm (Experiment 1), but had no effect on the formation of a Pavlovian conditioned inhibitor, (Experiment 2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
210
6
1

Year Published

1984
1984
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 469 publications
(237 citation statements)
references
References 43 publications
20
210
6
1
Order By: Relevance
“…However, several studies have identified structures that are not involved in conditioned inhibition. Lesions of the hippocampus or removal of the neocortex do not disrupt conditioned inhibition acquisition or retention (Moore, Yeo, Oakley, Russell, 1980;Solomon, 1977;Yeo, Hardiman, Moore, & Russell, 1983). Mis (1977) found that stimulation of the nucleus of Darkschewitsch, interstitial nucleus of Cajal, or anterior red nucleus inhibited CR production, and lesions of these areas prevented acquisition of conditioned inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies have identified structures that are not involved in conditioned inhibition. Lesions of the hippocampus or removal of the neocortex do not disrupt conditioned inhibition acquisition or retention (Moore, Yeo, Oakley, Russell, 1980;Solomon, 1977;Yeo, Hardiman, Moore, & Russell, 1983). Mis (1977) found that stimulation of the nucleus of Darkschewitsch, interstitial nucleus of Cajal, or anterior red nucleus inhibited CR production, and lesions of these areas prevented acquisition of conditioned inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…Supporting O'Keefe and Nadel's (1978) theory, conditioned inhibition seems to be absent only when it is mediated through the place or context in which the animal is trained (Micco & Schwartz, 1971), but not when it is mediated through a second CS (Solomon, 1977).…”
mentioning
confidence: 75%
“…Later on, this attentional control was proposed to underlie the psychological function of internal inhibition (Douglas, 1972;Douglas & Pribram, 1966;Kimble, 1968). The internal inhibition hypotheses find serious difficulties in the fact that hippocampal ablations do not affect the formation of conditioned inhibition when training consisted of a stimulus A, always reinforced, interspersed with stimuli A and B, always nonreinforced (Solomon, 1977). However, when the CS and the context signaled the absence of the US and the context alone signaled its presence (Micco & Schwartz, 1971), the development of conditioned inhibition was impaired.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations